INFLUENCE OF PRODUCT PLACEMENT IN MOVIES AND TELEVISION PROGRAMS TOWARDS BRAND RECALL OF MILLENNIALS - Parengkuan, Vega J. J.; Tulung, Joy E.; Arie, Fitty V. (Universitas Sam Ratulangi, 2020)
There are many changes that happens to entertainment medias, which forces marketers to evolve and adjust in order to advertise products. Nowadays, product placements are becoming a prominent marketing strategy used mostly in films and television programs. The purpose of this research is to analyze the influence of product placement in movies and television programs towards the brand recall of millennials in Manado by using variables such as: Visual Dimension, Auditory Dimension, and Plot Connection Dimension. This research uses quantitative method with questionnaires to collect the data, and Multiple Linear Regression as the tool of analysis. The samples in this research are 96 millennials in Manado, or people aged 20- 35 years old. The findings revealed that Visual Dimension have positive relationship and significant influence toward the Brand Recall, Auditory Dimension have negative relationship and no significant influence toward the Brand Recall, and Plot Connection Dimension have positive relationship and significant influence toward the Brand Recall. Marketers need to consider extending the visual prominence of their brand, increase the frequency of mention of the product to alert and notify the viewers, and have their product well integrated to the movie or television program’s storyline.Keywords: product placement, brand recall